2014
DOI: 10.1016/j.jand.2013.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Revised Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) Food Package Policy on Fruit and Vegetable Prices

Abstract: Obesity is generally inversely related to income among women in the United States. Less access to healthy foods is one way lower income can influence dietary behaviors and body weight. Federal food assistance programs, such as the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC), are an important source of healthy food for low-income populations. In 2009, as part of a nationwide policy revision, WIC added a fruit and vegetable (F/V) voucher to WIC food packages. This quasi-experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 24 publications
2
24
2
Order By: Relevance
“…These stores are important points of purchase in many lower-income and racial/ethnic minority neighbourhoods due to the lack of supermarkets. This finding supports other prior published studies showing small improvements in healthier food availability (and pricing) following the WIC food package revision (26)(27)(28)(29) . O'Malley et al examined the impact of the WIC food package revision using a new audit instrument, the WIC Availability Index (WIC-AI), and argue that their instrument is not only useful to monitor WIC adoption but also to measure the healthfulness of retail food environments in general.…”
Section: Food Availabilitysupporting
confidence: 92%
“…These stores are important points of purchase in many lower-income and racial/ethnic minority neighbourhoods due to the lack of supermarkets. This finding supports other prior published studies showing small improvements in healthier food availability (and pricing) following the WIC food package revision (26)(27)(28)(29) . O'Malley et al examined the impact of the WIC food package revision using a new audit instrument, the WIC Availability Index (WIC-AI), and argue that their instrument is not only useful to monitor WIC adoption but also to measure the healthfulness of retail food environments in general.…”
Section: Food Availabilitysupporting
confidence: 92%
“…These studies compare characteristics of the supply side (availability and prices) before and after the package change or the behavior of WIC participants (purchases and consumption) before and after the package change. The results from these studies consistently show that the availability of healthier foods included in the WIC package increased in stores (e.g., Andreyeva et al 2012;Ayala et al 2012) with some evidence that the prices of these foods did not rise or decreased (e.g., Zenk et al 2014). Further, these studies consistently find that the WIC package revision increased purchases and consumption of the foods included in the new package, resulting in an overall improvement in diet (e.g., Whaley et al 2012).…”
Section: Introductionmentioning
confidence: 57%
“…The investigators concluded that the federal policy changes to WIC had the intended effect of increasing consumption of the prescribed food items. In support of this finding, Zenk et al (2014) used a quasi-experimental design to determine whether F/V prices at WIC vendor stores decreased after the policy revision in seven Illinois counties. Results suggested that the WIC policy revision contributed to reductions in F/V prices.…”
Section: Prevention Of Obesitymentioning
confidence: 99%